Sag mir, wo die Blumen sind: zur Identifikation von Pflanzennamen in nepalischen Ritualtexten - Zotter, Astrid (Zeitschrift der Deutschen Morgenländischen Gesellschaft, 2016)
Identifying plants mentioned in Sanskrit texts botanically poses a number of problems. One of these results from the fact that, on the one hand, Sanskrit names circulate all over South Asia and over long periods, and on the other hand, the flora actually found at specific times and places differs. The present contribution reflects on the local and temporal variability of plant identification in a particular regional and thematic context. Drawing on a corpus of Nepalese texts stating rules for the use of flowers in worshipping Hindu deities, it is investigated how Sanskrit plant names are translated into the vernaculars, mainly Newari, and how they are identified with plants in ritual practice. The general analysis of the types of translations and of the blurred boundary between mistaken and creative exegesis is followed by four examples presented in more detail; i.e. Skt. śatapatra/śatapatrikā, tamālapatra, ketakī, and śamī. Two opposing tendencies can be observed, which, however, do not come into conflict, because they operate each on a different level. The tradition is conservative, as the authority of the Sanskrit texts is not questioned or altered. At the same time it is innovative, as species of local importance or those recently imported are included at the stage of translation into the vernaculars or on that of ritual implementation. The changing ritual flora can thus be legitimized by referring to an unchangeable textual authority. It is therefore argued that the much-bemoaned circumstance that in certain types of text plant names are only stated without any further hint to the corresponding species enhances the normative potential of the texts.
Gesehen am 15.04.2021